THE EFFECT OF EDUCATION LEVEL, INFRASTRUCTURE, AND POPULATION ON INTER-REGION DEVELOPMENT INEQUALITY - Ningsih, Idha Marta Kurnia; Mukhtar, Saparuddin; Iranto, Dicky (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This study aims to determine the effect of education level, infrastructure, and population on inter-region development inequality. The research method used in this study is a quantitative approach. The data used in this study are panel data from the five largest regions in Indonesia; Sumatra, Java, Kalimantan, Sulawesi and Papua from 2013 to 2022 which are collected through documentation techniques. The test results show that the variables of education level, road stability infrastructure, and infrastructure of households that have access to PLN electricity have a negative and significant effect on inter-region development inequality. Meanwhile, the total population variable has a significant positive effect on inter-region development inequality. Simultaneously, all research variables have a significant effect on inter-region development inequality. The coefficient of determination test in this study shows a 99% influence on development inequality and the remaining 1% is explained by other variables outside the study